Pengaruh Theraplay Terhadap Peningkatan Secure Attachment Anak Autism Specturm Disorder (ASD) dengan Orang tua - Martina Martina; Yuspendi Yuspendi; Meilani Rohinsa (Universitas Kristen Maranatha, 2025)
Parents with autism spectrum disorder (ASD) children have various challenges in raising children, it’s difficult to have a secure attachment with their children. This research was conducted to determine the effect of theraplay on increasing secure attachment in children with autism spectrum disorder (ASD) at the “X” therapy center in Bandung. Parents were given the Attachment Q-Sort (AQS) at the beginning, then given 12 sessions of theraplay intervention. After completion, parents were given the AQS again. The results showed that theraplay did not affect the attachment of ASD children at “X” therapy center in Bandung. There are several factors that influence the failure to change the attachment of children with ASD, including age, the number of sessions that are too short, and the activity design that does not meet the needs of each child.The researcher hopes that parents can spend more time interacting with their children consistently to change the attachment. Future researchers are expected to increase the number of sessions in order to see changes in parents’ attachment with ASD children.